Diagnosis and Treatment of Depression in Patients with Schizophrenia - Sergey N. Mosolov (Eco-Vector, 2020)
Depression is the third most common illness among patients with schizophrenia which negatively affects the course of the disease and significantly contributes to the mortality rate, due to increased suicide. Depression, along with negative symptoms and cognitive deficits, is one of the main factors that significantly decreases the quality of life and the disease prognosis in patients with schizophrenia. In addition, depression increases the frequency of exacerbations and readmissions, decreases the quality and duration of remissions and is associated with more frequent substance abuse and an increased economic burden. Data on the prevalence of depression among patients with schizophrenia are contradictory and are associated with a low detection rate of depression in such patients, a lack of clear diagnostic criteria and difficulties in differentiation between extrapyramidal and negative symptoms. The average prevalence of depression that meets the diagnostic criteria of major depressive episodes in patients with schizophrenia is 25% at a specific point, and 60% over the course of a lifetime; the frequency of subsyndromal depression is much higher. It is essential to distinguish between primary (axial syndrome) and secondary depressive symptoms (extrapyramidal symptoms, psychogenic or nosogenic reactions, social factors, etc.) to determine treatment strategies.